Agents and goals in evolution - Okasha, Samir (Oxford University Press, 2018)
Samir Okasha offers a critical study of agential thinking in biology, where evolved organisms are seen as agents pursuing a goal. He examines the justification for transposing concepts from rational humans to the biological world, and considers whether agential thinking is mere anthropomorphism or plays a more intellectual role in the science.